Le basculement vers le Sud de la politque de défense de l’Espagne (Note) - Santos, Alberto (Études internationales, 1985)
Entering the 21st century, the question facing mankind is whether we will be able to find, agree upon and activate solutions adequate to resolve world problems which have plagued the 20th century and which increasingly threaten the 21 st. The central argument presented here is that it is only by taking concrete steps at the world level that we can hope to reduce or eliminate the threat to survival which these problems represent.In order to provide a framework from which prospects for the future of the world organization can be analysed, the "world order" perspective is compared with a more traditional perspective. The challenges that world problems and crises pose for the world organization are examined. Using the fundamental changes undergone by both the League of Nations and the United Nations as an historical basis for scrutinizing the future, the changes that increasingly complex problems may force on the world organization are explored. Changes such as a "reinforced United Nations" (without delegation of sovereignty), a "World Authority" (with partial delegation of sovereignty) or a "World Government" (with major delegation of sovereignty) are evaluated in terms of the world organization' s ability to handle potential world crises and problems.The conclusion establishes that there is a pressing need for immediate political action which would aim towards a coalition of all groups researching solutions to world problems and would be based on the "world order" ideology of the majority rather than the "world-oriented" ideology of a self-interested minority.